The Convergent and Discriminant Validities between the IOR and the JDI: English and Spanish Forms - McCabe, Dennis J.; Dalessio, Anthony; Briga, Jānis; Sasaki, Julio (Academy of Management Journal, 1980)
The article discusses the merits of two instruments designed to determine levels of job satisfaction, the Job Descriptive Index (JDI) and the Index of Organizational Reactions (IOR). According to the author the purpose of this study is to determine whether or not responses to the Spanish forms of the two instruments were equivalent to those elicited by the English versions. The results of the study indicate that the instruments were successfully translated into Spanish, though the author believes future research should look to discover if both versions are similarly related in regards to employee turnover.